A Systematic Review of The Association Between Sedentary Behavior and Mental Health in Adolescence - Trimawati Trimawati; Mona Saparwati (Indonesian Journal of Nursing Research (IJNR), 2026)
Today's technological advancements provide convenience in various fields such as work activities, lifestyle, leisure time utilization and modern medicine. However, these technological advances also indirectly affect the decline in physical activity in general. Sedentary behavior occurs in all age ranges from children to the elderly. Children and adolescents are relevant age groups for this behavior because at this age there are a real physical and mental changes. One of the health consequences of sedentary behavior is mental health problems. This systematic review followed the PRISMA reference and applied review tools to assess quality and identify articles. Articles were obtained by searching PubMed, Springer Link and Scopus databases. From the search results, 9 suitable articles were obtained. Inclusion criteria include adolescence aged 10-19 yearas old, a quantitative studies, adolescents in general good health were included in the study due to the possible confounding effects of chronic physical health conditions. The most important part was that the negative impact of symptoms associated with these disorders could be recognizedThe 9 articles found that most adolescents experienced sedentary behavior and also health mental problem. The result of this study, 7/9 articles showed that the most common mental health was depression followed by anxiety. There is a relationship between sedentary behavior and mental health problems with the most common problem being depression